Facile fabrication and improved carbon dioxide tolerance of a novel bilayer-structured ceramic oxygen permeating membrane - Zhang, Z.; Chen, D.; Chen, Y.; Hao, Y.; Tade, Moses; Shao, Zongping (Elsevier BV, 2014)
An asymmetrical Ba0.5Sr0.5Co0.8Fe0.2O3-d (BSCF)|Pr0.5Ce0.5O2-d (PrCe) bilayer-structured ceramic membrane is fabricated by a facile technique involving dry pressing of BSCF substrate, wet spraying of PrCe thin film layer (~10 µm) and co-sintering of the bilayer structures. The phase reaction, sintering behavior and oxygen permeability of the membrane are systematically investigated using XRD, ESEM, EDX and oxygen permeation studies. The CO2 poisoning resistance of the layer materials is characterized by FTIR and CO2-TPD experiments. The large shrinkage of BSCF substrate and the diffusion of compositional elements from BSCF substrate into the PrCe layer promote the densification of PrCe layer at a temperature as low as 1100 °C. The as-fabricated bilayer membrane exhibits not only high oxygen permeation flux, reaching 1.6 mL cm-2 min-1 at 850 °C, but also favorable permeation stability even after the introduction of 10% CO2 into helium sweep gas. After the continuous operation at 850 °C under the CO2-containing atmosphere for 800 min, the permeation flux remains stable at around 1.35 mL cm-2 min-1. The facile fabrication and superiority of the bilayer-structured membrane in resistance towards CO2 poisoning thus provides a new way for the development of ceramic membranes for oxygen separation.